Arthroscopic All-Inside Repair of Medial Meniscus Grade 2 Horizontal Cleavage Tear Using Additional Posteromedial Portal - Thaunat, Mathieu (Arthrosc Tech, 2018)
Management of intrasubstance horizontal cleavage meniscal lesions of microtraumatic origin remains poorly defined in young patients. For grade 2 lesions resistant to conservative measures, the standard technique is debridement of the intrasubstance tear and open suture repair via a posteromedial approach. The objective of this Technical Note is to propose an arthroscopic alternative to this open technique, using an arthroscopic additional posteromedial portal. This technique facilitates an approach to the lesion via its peripheral portion without creating an iatrogenic lesion of the free edge of the meniscus, which is located in the white zone and thus exhibits limited vascularity.